The influence of cooling rate on condensation of iron, aluminum, and uranium oxide nanoparticles. (May 2022) - Koroglu, Batikan; Finko, Mikhail; Saggese, Chiara; Wagnon, Scott; Foster, Samuel; McGuffin, Dana; Lucas, Don; Rose, Tim P.; Crowhurst, Jonathan C.; Weisz, David G.; Radousky, Harry B.; Curreli, Davide; et al.
Abstract: Fundamental observations of particle size distributions are needed to develop models that predict the fate and transport of radioactive materials in the atmosphere following a nuclear incident. The extent of material transport is influenced by the time scales of particle formation processes (e.g., condensation, coagulation). In this study, we investigated the influence of cooling time scales on size distributions of uranium, aluminum, and iron oxide particles that are synthesized separately under identical run conditions inside the controlled environment of an argon plasma flow reactor. Two distinct temperature distributions are imposed along the flow reactor by varying the argon flow rate downstream of the plasma torch. The vaporized reactants of uranium, aluminum, and iron are cooled from about 5000 K to 1000 K before they are collected on silicon wafers for ex situ scanning electron microscope analysis. The microscope images show that the sizes of the largest aluminum and iron oxide particles heavily depend on the cooling time scales, whereas significant size variation with cooling rate is not observed for uranium oxide particles. In addition, the size distribution of aluminum oxide particles exhibits the broadest range among all three metal oxides studied. We performed simulations of particle size distributions using a kinetic model that couples gas phase oxidation chemistry with particle formation processes, including nucleation, condensation, and coagulation. The model results demonstrate the strong sensitivity of particle size distribution to different cooling histories (i.e., temperature vs residence time) along the flow reactor. The kinetic model also helps identify directions for future research to improve the predictions. Highlights: The kinetic model results demonstrate the strong sensitivity of particle size distribution to different cooling histories. The largest sizes of aluminum and iron oxide nanoparticles decrease by increasing the rate of temperature drop. Aluminum oxide nanoparticles exhibit the broadest size range among all three metal oxides studied